Using next-generation sequencing approach for discovery and characterization of plant molecular markers - Bahman Panahi; Hossein Mohammadzadeh Jalaly; Rasmieh Hamid (Current Plant Biology)
Crop development is critical to meeting the world's growing food needs, especially in light of the challenges posed by climate change and population growth. Molecular markers (MM) have become an indispensable tool in breeding programmes as they enable rapid trait selection and monitoring of genetic variation. Next generation sequencing (NGS) has transformed genomics by providing low-cost, high-throughput technologies for the identification of markers in plants. This review focuses on the latest applications, advances and opportunities of NGS in the discovery and characterization of MM in plants. We have addressed the involvement of NGS in the detection of different types of markers such as single nucleotide polymorphisms (SNPs), indels, simple sequence repeats (SSRs) and structural variants (SVs) and their applications in functional genomics and plant breeding. We have also demonstrated the possibility of combining NGS with modern bioinformatics techniques to accelerate the development of markers and improve crop resistance and yield.